Unique Impact of Library Services Based On Timezone: Case Study in Sekolah Dasar Islam Terpadu (SDIT) Alam Nurul Islam Sleman - Yahya Riawan; Aris Suharyadi; Salman Rashid (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2025)
This study aims to describe: (1) the implementation of timezone services in the SDIT Alam Nurul Islam library, (2) their impact on library uses and student engagement, and (3) the challenges involved in their implementation. A qualitative descriptive approach was employed. This research was conducted at SDIT Alam Nurul Islam, Sleman Regency. The subjects of this study included school principals, teachers, librarians, and students. The results of the study concluded: 1) The implementation of time zones aims to increase student interest in libraries. It features both educational and traditional games, which are either made in-house or purchased. The most popular games among students are spinning tops and checkers.2) The positive impact is that it influences student interest and does not directly impact interest in reading and learning while a drawback is that some students become late to class due to extended playtime. 3) Implementation challenges include internal issues such as difficulties in creating games and limited space, and external issues related to student behavior. Research results show that the timezone service has a significant positive impact: (1) increasing students' enthusiasm to visit the library regularly, (2) fostering students' reading interest through targeted game media, and (3) becoming an educational entertainment alternative that supports a pleasant learning atmosphere at school. This innovation also encourages the role of the library as a child-friendly and inspiring literacy activity center. Thus, the timezone service can serve as a model for creative services that can be implemented in other elementary school libraries.